Pharmacogenetic interactions of rifapentine plus isoniazid with efavirenz or nevirapine. Issue 1 (January 2021) - Haas, David W.; Podany, Anthony T.; Bao, Yajing; Swindells, Susan; Chaisson, Richard E.; Mwelase, Noluthando; Supparatpinyo, Khuanchai; Mohapi, Lerato; Gupta, Amita; Benson, Constance A.; Baker, Paxton; Fletcher, Courtney V.
Abstract : Objectives: The effect of rifapentine plus isoniazid on efavirenz pharmacokinetics was characterized in AIDS Clinical Trials Group protocol A5279 (NCT01404312). The present analyses characterize pharmacogenetic interactions between these drugs, and with nevirapine. Methods: A subset of HIV-positive individuals receiving efavirenz- or nevirapine-containing antiretroviral therapy in A5279 underwent pharmacokinetic evaluations at baseline, and again weeks 2 and 4 after initiating daily rifapentine plus isoniazid. Associations with polymorphisms relevant to efavirenz, nevirapine, isoniazid, and rifapentine pharmacokinetics were assessed. Results: Of 128 participants, 101 were evaluable for associations with rifapentine and its active 25-desacetyl metabolite, 87 with efavirenz, and 38 with nevirapine. In multivariable analyses, NAT2 slow acetylators had greater week 4 plasma concentrations of rifapentine ( P  = 2.6 × 10 −3 ) and 25-desacetyl rifapentine ( P  = 7.0 × 10 −5 ) among all participants, and in efavirenz and nevirapine subgroups. NAT2 slow acetylators also had greater plasma efavirenz and nevirapine concentration increases from baseline to week 4, and greater decreases from baseline in clearance. CYP2B6 poor metabolizers had greater efavirenz concentrations at all weeks and greater nevirapine concentrations at baseline. None of 47 additional polymorphisms in 11 genes were significantly associated with pharmacokinetics. Conclusions: Among HIV-positive individuals receiving efavirenz or nevirapine, and who then initiated rifapentine plus isoniazid in A5279, NAT2 slow acetylators had greater rifapentine and 25-desacetyl rifapentine concentrations, and greater increases from baseline in plasma efavirenz and nevirapine concentrations. These associations are likely mediated by greater isoniazid exposure in NAT2 slow acetylators. Abstract : Supplemental Digital Content is available in the text.